ANALISIS SEMIOTIKA DALAM PESAN MORAL FILM THE EAST - Sekar Putri; Sukma Sulpajri (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Abstract : The East film is set in 1946 when the Netherlands entered the Indonesian national revolution period. A young soldier named Johan was fascinated by Army captain Raymond Westerling who led a counter-insurgency operation against Indonesian guerrillas and a clean-up operation in South Sulawesi, but gradually Johan began to question himself more and more about war. This type of research is descriptive qualitative research that uses data collection techniques, observation, documentation. While the data analysis technique is the content analysis model, by reducing data, displaying data, verifying or drawing conclusions. The results of the study show that the film The East has a hidden or visible moral message in every scan, both verbally and visually. The results are in accordance with Charles Sanders Pierce's semiotic signs in the form of Representament (Icon, Index, symbol), Object, Interpretant. Keywords: moral message, semiotics, Object Representament, Interpretant.